Investigating and Analyzing the Factors Affecting the Development of Agricultural Entrepreneurship in Rural Areas of Iranshahr County with the AHP Analysis Approach - Mohim Sheihaki Tash; Abubakr Raeisi; Louqman Mansouri (International Journal of Supply Chain Management, 2018)
Apart from the policies and macro strategies of economic development, the pundits of rural development pay special attention to the development of villages and the eradication of the widespread poverty prevailing them. Because, according to economists, this is the most important factor in the economic development of the villages and the agricultural sector and according to politicians, the development of agricultural entrepreneurship in villages is a key strategy for preventing social harm. Accordingly, the aim of this study is to identify and prioritize the factors affecting the development of agricultural entrepreneurship in rural areas of Iranshahr County using the AHP approach from the viewpoint of entrepreneurship farmers and agricultural experts. In terms of method, this research is of descriptive - survey type and in terms of objective it is an applied research. The statistical population of this research includes 60 farmers and agricultural experts of Iranshahr County. Out of 60 persons, 52 persons were selected as the sample using a Cochran formula. The survey instrument was a questionnaire, the validity of which was confirmed by a group of agricultural experts and its reliability was estimated about 0.783 using Cronbach's alpha coefficient. Data were analyzed using SPSS 23 software package and in order for ranking them the multi criteria decision making was used. Based on the results, five factors of environmental, social, economic, behavioral and promotional have played a role in the development of agricultural entrepreneurship among which the economic factors with the weight of 0.290 have had the greatest impact on agricultural entrepreneurship followed by behavioral, environmental, promotional and social factors with weights of 0.201, 0.199, 0.169, 0.142, respectively.